Mental health impacts of nurses caring for patients with COVID-19 in Peru: Fear of contagion, generalized anxiety, and physical-cognitive fatigue - Becerra-Medina, Lucy Tani; Meneses-La-Riva, Monica Elisa; Ruíz-Ruíz, María Teresa; Marcilla-Félix, Aquilina; Suyo-Vega, Josefina Amanda; Fernández-Bedoya, Víctor Hugo (Frontiers in Psychology, 2022)
The health crisis caused by Covid-19 has resulted in the physical and emotional deterioration of health personnel, especially nurses, whose emotional state is affected by the high risk of contagion, the high demands of health services, and the exhausting working hours. The objective of this research was to determine the relationship between fear, anxiety and fatigue of nurses caring for patients with Covid-19 in second level public hospitals in Peru (country with one of the highest numbers of deaths from this disease). The study presents a quantitative approach, correlational level, cross-sectional and non-experimental design. The sample consisted of 145 nurses who attended patients with Covid-19 in health care areas. The results show a significant relationship between fear of contagion and physical-cognitive fatigue (p<0.001; r=317), and a significant relationship between generalized anxiety and physical-cognitive fatigue (p<0.001; r=480). It is concluded that in this context, both fear of contagion and generalized anxiety are related to physical-cognitive fatigue.